The Impossible Subject of Suicide : Challenging Suicide Prevention - Saartje Tack (Routledge, 2026)
Deploying feminist and queer theories of embodiment and subjectivity, The Impossible Subject of Suicide stages an intervention into dominant understandings of suicide that position suicide prevention as the only possible and ethical response to suicide, thus ruling it out as a legitimate choice.With attention to scholarly research, news media, fiction, public health, and social media, the author investigates the cultural mechanisms at play in positioning and sustaining suicide prevention as a pre-discursive, a-contextual, and natural response to suicide. As the prevention narrative relies on the assumption that'normal,''healthy,'and'rational'people want to live, it relegates the suicidal subject to de-agentified subject positions such as mentally ill, at-risk, or vulnerable, and thus effectively silences those who consider death. As such, the suicidal subject cannot exist as a subject in its own right: it is an impossible subject.A study of the ways in which the subject's agency is conditioned by the expression of a normative desire to live, this book interrogates the taken-for-granted knowledges of suicide that have for decades informed understandings and representations of suicide, and aims to render the lives of those who live with suicide more liveable and open up a space from which those who have culturally been silenced can speak. It will, therefore, appeal to scholars in the social sciences and humanities with an interest in mental health, suicide, and/or questions around agency, embodiment, and subjectivity.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.